2010
DOI: 10.1128/aem.02183-09
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Swine Manure on Macrolide, Lincosamide, and Streptogramin B Antimicrobial Resistance in Soils

Abstract: Current agricultural practices involve inclusion of antimicrobials in animal feed and result in manure containing antimicrobials and antimicrobial-resistant microorganisms. This work evaluated the effects of land application of swine manure on the levels of tetracycline, macrolide, and lincosamide antimicrobials and on macrolide, lincosamide, and streptogramin B (MLS B ) resistance in field soil samples and laboratory soil batch tests. MLS B and tetracycline antimicrobials were quantified after solid-phase ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 33 publications
3
20
1
Order By: Relevance
“…Only a transient (< 20-day) MLS B resistance increase was documented in most batch tests. In contrast to other studies, Zhou et al (2010) did not detect a persistent increase in the occurrence of MLS B resistance due to land application of treated swine manure. Mindlin et al (2008) generated a collection of antibiotic resistant bacterial strains isolated from arctic permafrost subsoil sediments of various age and genesis.…”
Section: Antibiotic Resistance In Terrestrial Habitatscontrasting
confidence: 79%
See 1 more Smart Citation
“…Only a transient (< 20-day) MLS B resistance increase was documented in most batch tests. In contrast to other studies, Zhou et al (2010) did not detect a persistent increase in the occurrence of MLS B resistance due to land application of treated swine manure. Mindlin et al (2008) generated a collection of antibiotic resistant bacterial strains isolated from arctic permafrost subsoil sediments of various age and genesis.…”
Section: Antibiotic Resistance In Terrestrial Habitatscontrasting
confidence: 79%
“…Thus, this study provided the first description of the genotypes sul1, sul2, and sul3 outside the Enterobacteriaceae and in the soil environment. Zhou et al (2010) evaluated the effects of land application of swine manure on the levels of tetracycline, macrolide, and lincosamide antibiotics and on MLS B resistance in field soil samples and laboratory soil batch tests. MLS B and tetracycline antimicrobials were quantified by liquid chromatography-tandem mass spectrometry, the prevalence of the ribosomal modification responsible for MLS B resistance in the samples was quantified by fluorescence in situ hybridization (FISH).…”
Section: Antibiotic Resistance In Terrestrial Habitatsmentioning
confidence: 99%
“…Although chemical fertilizer had some effects on soil ARGs, these effects, not surprisingly, are weaker when compared with sewage sludge or chicken manure, considering that manure is rich in ARGs and ARBs , Jiang et al, 2002Ghosh and LaPara, 2007) and most ARGs are discharged from the municipal wastewater treatment process in the form of sewage sludge (Munir et al, 2011). However, land application of animal manure or sewage sludge does not universally increase ARGs in soils (Zhou et al, 2010) and this increase is not maintained long-term (Fahrenfeld et al, 2014). For instance, manure from three dairy farms did not increase cultivable chlortetracycline-resistant bacteria when land-applied to soil (Ghosh and LaPara, 2007).…”
Section: Responses Of Args Abundance and Compositionmentioning
confidence: 99%
“…Similarly, Sengelov et al (2003) observed an increased tetracycline resistance in soil after swine manure application, and this increase remained elevated for up to five months. By contrast, some studies showed that the increase of resistance was transient and returned to baseline levels a few dozens of days after manure application (Byrne-Bailey et al, 2009;Zhou et al, 2010;Fahrenfeld et al, 2014). It has been generally thought that the persistence of antibiotic resistance in soil depended on the environmental selection of "native" resistance, the relative growth and decay of manure-associated bacteria, and the tendency for horizontal gene transfer.…”
Section: Occurrence and Levels Of Pmqr Genes In Soilmentioning
confidence: 88%